The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/1908065
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Immunotherapy in Patients with Metastatic Mucosal or Uveal Melanoma

Abstract: Background The objective was to assess the response rate and survival of patients with metastatic mucosal melanoma (MM) and uveal melanoma (UM) treated with anti-CTLA-4 or anti-PD-1 monoclonal antibodies (mAbs). Methods A multicenter retrospective study was performed in 25 dermatology departments in France. All patients with stage III-C to IV MM or UM who were treated with anti-CTLA-4 or anti-PD-1 mAbs between 2008 and 2016 were included and compared after adjustment for main prognostic factors with a second c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…Immune checkpoint inhibitors, such as ipilimumab, nivolumab, and pembrolizumab, achieve long-term OS with 5-year OS rates of 34–52% in metastatic cutaneous melanoma [ 7 9 ] but yield poor outcome results in metastatic uveal melanoma (UM) with a median OS of 10–14 months [ 10 13 ]. At present, there is no standard therapy for metastatic UM, and the limited activity of systemic therapy compared with cutaneous melanoma poses a treatment challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint inhibitors, such as ipilimumab, nivolumab, and pembrolizumab, achieve long-term OS with 5-year OS rates of 34–52% in metastatic cutaneous melanoma [ 7 9 ] but yield poor outcome results in metastatic uveal melanoma (UM) with a median OS of 10–14 months [ 10 13 ]. At present, there is no standard therapy for metastatic UM, and the limited activity of systemic therapy compared with cutaneous melanoma poses a treatment challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In a French retrospective study [57], 210 patients with metastatic UM were treated with the anti-CTLA-4 antibody ipilimumab or the anti-PD-1 antibodies nivolumab or pembrolizumab. No partial or complete response of metastases was observed.…”
Section: Uveal Melanomamentioning
confidence: 99%
“…The OS of mucosal melanoma patients treated with CPIs appeared to be longer than that of patients treated with chemotherapy, with a median OS of 15.97 months and 8.82 months, respectively. In conclusion, immunotherapy appears to improve overall survival for patients with metastatic mucosal melanoma [57]. In a pooled analysis [63], the outcome of patients with metastatic mucosal melanoma treated in trials either with single-agent nivolumab (n = 86) or the combination of nivolumab and ipilimumab (n = 35) was reported.…”
Section: Mucosal Melanomamentioning
confidence: 99%
“…The efficacy achieved in the management of metastatic cutaneous melanoma and other cancers with reported durable response rates ranging from 20 to over 60%, has not been observed in mUM [ 205 , 206 , 207 ]. Studies reported a response rate below 10%, and a median survival less of than 1 year with a single-agent checkpoint block have been widely described [ 208 , 209 , 210 , 211 , 212 , 213 ]. This is likely related to the immune privilege of the eye, which establishes mechanisms to evade the immune system, and with the low mutational load with limited potential neoepitopes of UM if compared with cutaneous melanoma.…”
Section: Treatment Of Metastatic Diseasementioning
confidence: 99%